THE ROLE OF PUBLIC OPINION OF GREAT BRITAIN OF THE SECOND HALF OF THE 19TH CENTURY IN THE DEVELOPMENT OF THE SOCIAL LEGISLATION IN YEARS 1870-1890 OF QUEEN VICTORIA’S REIGN - J. D. Tsvetkova (Vestnik MGIMO-Universiteta)
Using primary sources in Russian and British historiography, the author analyzes the evolution of public thought in Great Britain in the second half of the 19th century, its turn from individualism and principle of “night-watchman state” to a more socially-oriented position. This transformation, which occurred under the influence of both evident and hidden factors, was one of the key prerequisites for formation in the seventh decade of the 19th century of the New Toryism and “social liberalism” doctrines, the framework of which was used by the British government to chart a course for systematic social reforms in the areas of health care, elementary education, residential development and labor law. By analyzing the views of J. Bentham, J.S. Mill and T.H. Green, as well as literary works of the period in question, the author traces the process of alienation of the “laissez-faire” policy (the classical principle of state non-interference in economy) by a certain part of the British society and the readiness to reassess the role of the state in the social sphere. The article presents in detail the search for philosophical, social and socialistic thought, aimed at solving the deepest social problems and predicating, in many aspects, the cycle of social reforms carried out by the Disraeli and Gladstone cabinets under the auspices of the state in the middle of the late Victorian period. The author points out that the social policy of the prime ministers W. Gladstone in 1868-1874 and B. Disraeli in 1874-1800 was historically the first precedent when the liberal doctrine which took the shape of the so-called Manchester liberalism in Great Britain had to recognize the principles of social state, economic regulation and a stronger role of the state in the British society. The author notes that the foundations of most of the social reforms that are now perceived as integral components of a modern democratic society were laid precisely in this historical period. Thanks to the flexibility of the English establishment, that was able to assess the strength of public opinion and to offer social doctrines aimed at meeting the growing social demands, the British government demonstrated the art of subtle political maneuver and the possibility of a bloodless way of carrying out social reforms.